The Unforeseen Diagnosis: Hyperparathyroidism-Jaw Tumour Syndrome Case Report and Review of the Literature - Maxim Barnett; Farhan Ahmed; Radu Mihai; Asha Rattan; Malik Asif Humayun (Case Reports in Endocrinology)
Hypercalcaemia and its systemic sequelae are a relatively common finding amongst patients in the field of endocrinology. Primary hyperparathyroidism, a frequent cause of hypercalcaemia, is often seen among middle-aged female patients, typically resulting from an underlying single-gland adenoma. Although patients may present with symptoms (nephrolithiasis, musculoskeletal discomfort, dehydration, or mood disturbance, to name a few), hypercalcaemia is rather frequently identified incidentally. In younger patients, a familial form of primary hyperparathyroidism must be considered, with a positive diagnosis mandating familial screening. Hyperparathyroidism-jaw tumour syndrome is one such autosomal dominant familial disorder, characterised by a mutation in the cell division cycle 73 (CDC73; also known as HRPT-2) tumour suppressor gene. This disorder is characterised by multiple pleiotropic phenomena, including recurrent primary hyperparathyroidism (and the effects of hypercalcaemia), neoplasms (such as uterine, renal, mandibular, and maxillary), and infertility. A patient not conforming to the classic candidacy for primary hyperparathyroidism requires consideration for a familial cause. Case Description. We present a rare diagnostic entity—hyperparathyroidism-jaw tumour (HPT-JT) syndrome—in a 36-year-old female with recurrent primary hyperparathyroidism, frequent nephrolithiasis, and infertility for 18 years prior to the diagnosis. We aim to promote awareness amongst medical professionals of this rare, but nonetheless essential differential diagnosis through a case report and review of the literature. Conclusion. Medical professionals must avoid diagnostic overshadowing and display a low threshold for genetic testing in younger patients with primary hyperparathyroidism. The importance of proper identification extends beyond the patient to their relatives and offspring.